2019
DOI: 10.1177/1524838019882023
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Access to Emergency Contraception for Sexual Assault Victims in Emergency Departments in the United States

Abstract: Objective: We conducted a scoping review of the literature to assess the prevalence of hospital policies regarding emergency contraception (EC) and the frequency that U.S. emergency departments (EDs) provide EC to sexual assault survivors. Study Design: We searched PubMed, Embase, the Cochrane Library, and CINAHL from inception to January 2019 for studies that assessed access to EC for sexual assault survivors in EDs. We included English-language studies that surveyed ED staff at U.S. hospitals and reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…196 Other studies did not find a similar link, but it is currently recognized that even if there may not be an impact on the rate of abortions at the population level, access to EC lowers abortion rates at the individual level. 197 As part of reducing barriers to access, it is critical to safeguard the protection of special populations, including adolescents, 57,198 non-English speaking patients, 198 individuals at hospitals with religious affiliation, 199,200 sexual assault survivors, 201 women facing disaster situations, 202 patients from rural areas, 203 and military and veteran populations. 131,204…”
Section: Misinformationmentioning
confidence: 99%
“…196 Other studies did not find a similar link, but it is currently recognized that even if there may not be an impact on the rate of abortions at the population level, access to EC lowers abortion rates at the individual level. 197 As part of reducing barriers to access, it is critical to safeguard the protection of special populations, including adolescents, 57,198 non-English speaking patients, 198 individuals at hospitals with religious affiliation, 199,200 sexual assault survivors, 201 women facing disaster situations, 202 patients from rural areas, 203 and military and veteran populations. 131,204…”
Section: Misinformationmentioning
confidence: 99%
“…Sexual assault survivors are at significant risk of unintended pregnancy. Many of these individuals present to emergency departments for care in the period that EC can be most effective in preventing unintended pregnancy; however, hospital policies concerning EC, staff misconceptions or objections, and/or state laws regarding EC can affect patient access 19 . Studies found inconsistency in hospital policies regarding access to EC.…”
Section: Barriers To Using Emergency Contraceptionmentioning
confidence: 99%